From welfare to farewell: The European social-ecological state beyond economic growth - Éloi Laurent (European Trade Union Institute (ETUI), 2021)
This working paper is intended to shed light on a pressing issue: the apparent growth-dependency of European welfare states at a time of weak growth prospects and strong criticisms of growth. Indeed, while the notion of going beyond GDP growth is gaining momentum in the European Union, as elsewhere, and seems rational and desirable to a growing number of citizens and policymakers, it might not be feasible. Highlighting a new 'welfare-growth-transition trilemma', I first show how European welfare states in the twentieth century were based on a social-economic alliance that was largely blind to mounting environmental challenges that were likely to undermine their financial sustainability. I then explore the link, too often taken for granted, between GDP growth, human well-being and social progress (focusing on employment, inequality and health), and review empirical evidence supporting the growth-dependency of the welfare state hypothesis (focusing on health care and pensions), reaching the conclusion that these relations appear fragile. I then question the need for additional growth in the perspective of climate transition and offer two alternative strategies: progressive social-ecological taxation and social savings induced by environmental policy. I finally insist on the need to turn the welfare state into a 'social-ecological state' in the face of the growing human impact of climate change and to a develop social-ecological protection (focusing on old age and heatwaves).
Keywords: 330; welfare state; economic growth; impact analysis; EU countries; Sozialstaat; Wirtschaftswachstum; Wirkungsanalyse; EU-Staaten